2017
DOI: 10.1111/1753-0407.12614
|View full text |Cite
|
Sign up to set email alerts
|

Resistance training reduces metabolic syndrome and inflammatory markers in older women: A randomized controlled trial

Abstract: The results suggest that a 12-week RT program seems to effectively reduce MetS components and inflammatory biomarkers in older women, regardless of dietary intervention. The RT-induced adaptations in body composition and inflammatory biomarkers appear to be related to healthy adaptations in risk factors for MetS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 44 publications
2
77
0
3
Order By: Relevance
“…A sample size estimation was conducted using G * Power (version 3.0.10, Universität Kiel, Germany). Fat mass data was used from previous studies conducted by our research team using RT interventions [36,37,46,47] for sample size calculation. A median effect size of 0.23, an α level of 0.05, and a power (1 - β) of 0.80, indicated 51 volunteers would be required (17 subjects per group).…”
Section: Participantsmentioning
confidence: 99%
“…A sample size estimation was conducted using G * Power (version 3.0.10, Universität Kiel, Germany). Fat mass data was used from previous studies conducted by our research team using RT interventions [36,37,46,47] for sample size calculation. A median effect size of 0.23, an α level of 0.05, and a power (1 - β) of 0.80, indicated 51 volunteers would be required (17 subjects per group).…”
Section: Participantsmentioning
confidence: 99%
“…It is noteworthy that investigations [ 50 , 51 ] that approached a resistance component performed at higher intensities than was used in the current study observed a significant decrease in blood pressure values, which was associated with significant alterations in inflammatory markers (i.e., C-reactive protein and TNF- α ), NO bioavailability, and fat mass. Regarding the aerobic component, studies using a larger frequency, volume, and intensity when compared to our MCEP have demonstrated regulation of ROS production and an increase in NO levels [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 54%
“…Of interest is a prior publication of ours from CLIP‐II showing that the WL + RT group lost less lean mass than either WL + AT or WL . Also, an RT study with older women with MetS found that the reduction in CRP with training was related to increases in muscle mass , results that parallel a 12‐month RT intervention among older adults with type 2 diabetes . It is also known that increases in IL‐6 released by muscle during contraction have an anti‐inflammatory effect in opposition to the IL‐6 released by visceral adiposity, which is proinflammatory .…”
Section: Discussionmentioning
confidence: 95%